Closed-Form Expression for the Bit Error Probability of the M-QAM for a Channel Subjected to Impulsive Noise and Nakagami Fading. (21st October 2018) - Silva, Hugerles S.; Alencar, Marcelo S.; Queiroz, Wamberto J. L.; Almeida, Danilo B. T.; Madeiro, Francisco
Abstract : In this paper, new exact expressions for evaluating the bit error probability (BEP) of the M -ary quadrature amplitude modulation scheme (M -QAM) for a channel model characterized by double gated additive white Gaussian noise (G 2 AWGN) and Nakagami fading are presented. The derivation of the BEP is performed considering a method in which the multiplicative fading is transformed in an additive noise R obtained by dividing the received signal by the estimated fading envelope. In addition, the probability density function (PDF) and cumulative density function (CDF) of the random variable R that represents the aforementioned noise are obtained for the G 2 AWGN. The BEP curves as a function of the signal to permanent noise ratio for several values of the signal to impulsive noise ratio, modulation order, and fading parameters are also presented.